2020
DOI: 10.1016/j.jstrokecerebrovasdis.2020.105231
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Cerebral Ischemia in A COVID-19 Infected Patient: Case Review and Histopathological Findings

Abstract: Severe acute respiratory syndrome coronavirus (SARS-CoV-2) is responsible for an unprecedented worldwide pandemic that has severely impacted the United States. As the pandemic continues, a growing body of evidence suggests that infected patients may develop significant coagulopathy with resultant thromboembolic complications including deep vein thrombosis, pulmonary embolism, myocardial infarction, and ischemic stroke. However, this data is limited and comes from recent small case series and observational stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 18 publications
(24 reference statements)
0
20
0
2
Order By: Relevance
“…The authors suggested that the cerebrovascular thromboembolic events in COVID-19 infection may be related to acquired hypercoagulability and coagulation cascade activation due to the release of inflammatory markers and cytokines, rather than virus-induced vasculitis. Microthrombi within the vessels were more consistent with a systemic inflammatory response-mediated mechanism, probably related to elevated serum inflammatory markers such as D-dimer and fibrinogen (31,32).…”
Section: Mechanisms Of Covid-19-mediated Cerebrovascular Complicationsmentioning
confidence: 84%
See 1 more Smart Citation
“…The authors suggested that the cerebrovascular thromboembolic events in COVID-19 infection may be related to acquired hypercoagulability and coagulation cascade activation due to the release of inflammatory markers and cytokines, rather than virus-induced vasculitis. Microthrombi within the vessels were more consistent with a systemic inflammatory response-mediated mechanism, probably related to elevated serum inflammatory markers such as D-dimer and fibrinogen (31,32).…”
Section: Mechanisms Of Covid-19-mediated Cerebrovascular Complicationsmentioning
confidence: 84%
“…Evidence suggests that infected patients may develop significant coagulopathy which leads to thromboembolic complications like stroke, peripheral artery thrombosis, deep vein thrombosis, pulmonary embolism, myocardial infarction, ischemic stroke, and venous sinus thrombosis (29,30). Histopathologic analysis of the ischemic brain of a COVID-19 patient revealed hypoxic neurons, significant edema from the underlying ischemic insult, fibrin thrombi in small vessels, and fibroid necrosis of the vascular wall without any signs of vasculature inflammation (31). The authors suggested that the cerebrovascular thromboembolic events in COVID-19 infection may be related to acquired hypercoagulability and coagulation cascade activation due to the release of inflammatory markers and cytokines, rather than virus-induced vasculitis.…”
Section: Mechanisms Of Covid-19-mediated Cerebrovascular Complicationsmentioning
confidence: 99%
“…Attenuation and effacement at the right hemisphere around the Sylvian fissure Case 3. Hypo-density at left basal ganglion 41 Locked-in with COVID-19 [ 47 ] MRI—brain MRA Numerous foci of restricted diffusion within the pons, (correlating with FLAIR signal abnormality) consistent with acute pontine ischemic infarcts Decreased flow in distal right vertebral artery with a patent basilar artery 42 Macrothrombosis and stroke in patients with mild COVID-19 infection [ 48 ] CT—head MRI—brain Nonocclusive thrombus in the right common carotid artery, extending into the ICA Acute stroke in the territory of the right MCA 43 Malignant cerebral ischemia in a COVID-19 infected patient: case review and histopathological findings [ 49 ] CT—head Large right MCA infarct 44 Multiple sclerosis following SARS-CoV-2 infection [ 50 ] MRI—brain Supratentorial periventricular demyelinating lesions in right occipital lobe and left temporal 45 Necessity of brain imaging in COVID-19 infected patients presenting with acute neurological deficits [ 51 ] CT—head Case 1—B/L subacute infarcts, basilar cistern effacement, a left-to-right midline shift, intraparenchymal hemorrhage, sub-falcine, and uncal herniation Case 2—Pre-op - large volume hemorrhage within the right temporal and parietal lobes, surrounding edema, midline shift, uncal herniation, and entrapment of the temporal horns. Post-op—right-sided craniectomy and anterior temporal lobectomy—improvement in overall mass effect 46 Neuralgic amyotrophy following infection with SARS-CoV-2 [ 52 ] MRI—brain Edema and inflammatory contrast enhancement of the right distal median nerve Minor right C5-C6 disk protrusion without nerve root impingement, and mild T2-signal increase of the ipsilateral C7-C8 roots, suggestive of proximal edema 47 Neurological manifestations in critically ill patients with COVID-19: a retrospective study [ 53 ] CT—head Low density lesions in the following: Case 1.…”
Section: Resultsmentioning
confidence: 99%
“…[ 29 ] What is even more alarming are reports of stroke in COVID-19 patients younger than 50 years of age. [ 16 , 20 , 23 , 24 , 26 , 28 ] Before the COVID-19 pandemic, the average age of a patient with ischemic stroke was 66 (±12) years,[ 22 ] but the average age in this series was nearly two decades younger at 48 (±11) years.…”
Section: Discussionmentioning
confidence: 99%